Malaysian legal systems and adversarial trial - Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan (CLJ Malaysia Sdn. Bhd., 2025)
this chapter aims to explore the salient features of the common law system and the Islamic legal system as practised in Malaysia, and further highlight the procedure for criminal and civil trials and legal representation. The above discussion is necessary to better appreciate the practice of the dual legal profession and trial process in this country.